STUDY OF LEAD CONTAINING IN DUG WELL WATER AT SUKAWINATAN DUMPING SITE IN PALEMBANG CITY - Maksuk; Suzanna (Faculty of Public Health, Sriwijaya University, 2018)
Background: The dumping site is the end place to stock up on various types of waste. 0ne of them is heavy metals such as lead. Lead is one of heavy metal that is very toxic to human mainly children. This study aims to analyse lead containing in dug wells water of community around at the dumping site. Method: This research was a analytical descriptive with cross sectional design. The samples of dug wells water were taken from 5 spots distance from waste dumping location, they were 100 metres, 200 metres, 300 metres, 400 metres and 500 metres, so total samples were 15. The sampling technique was purposive sampling. Lead containing was examined in laboratory by Atomic Absorption Spectrometry (AAS) with SNI 6969.8.2000 method. pH and temperature measurements were tested in situ, while for physical qualities of dug well water was observed by check list. Results: The results of observation that the dug wells construction were not qualified construction as many as 93,3% , but physical qualities of dug well water were qualified. The average of lead containing in dug well water was 0.03 mg / L, with range were between 0.012-0.052 mg / L, while the pH of dug well water were between 3.2 - 6.7, it was classified as acid. Namun jika dibandingkan dengan persyaratan air minum kadar timbal dalam sumur gali tidak memenuhi syarat. Conclusion: Lead containing was found in dug well water was safe, but there was one of dug well water that was above environmental quality standards. However, when compared with drinking water requirements, lead levels in dug wells were not qualified. Therefore it is necessary the participation of community and role of local government was needed to treatment the dug well water before using it and improving contruction of dug well.